A systematic study of PPLN length dependence in intracavity SHG - Tyler Kashak (Nature Portfolio, 2021)
Abstract In this paper, a systematic study of the relationship between nonlinear crystal length and intracavity second-harmonic generation (SHG) using MgO-doped periodically-poled lithium niobate (MgO:PPLN) is presented. The experimental results demonstrate a relationship between the maximum SHG power generated and the full-width at half maximum (FWHM) of the crystal’s temperature tuning curve to the length of the nonlinear optical crystal. It was shown that maximum SHG power increases rapidly with the increase of MgO:PPLN length, reaching a saturation length (~ 2 mm), which is much shorter than that predicted by the single-pass SHG theory. This saturation length of the MgO:PPLN crystal is almost independent on 808 nm pump power for typical powers used in continuous wave intracavity SHG lasers. In addition to this saturation effect, a broadening effect was also observed, the FWHM of the temperature tuning curve was shown to have a larger FWHM than that predicted by the single-pass SHG theory for MgO:PPLN shorter than the saturation length. This work has the benefit of allowing engineers to optimize nonlinear crystal length when developing intracavity SHG based diode-pumped solid state (DPSS) lasers.